Relationship between microscopic analysis and quantitative and qualitative indicators of moisture susceptibility evaluation of warm-mix asphalt mixtures containing modifiers (Fracture and Structural Integrity, 2019)
Given the defects of bitumen in asphalt mixtures particularly exposed to moisture, this study mainly aims to investigate the relationship between qualitative and quantitative results of moisture susceptibility tests on asphalt mixtures modified by ZycoTherm, nanoclay, nanosilica and SBS. The Marshall stability, modulus of resilience and indirect tensile strength tests are carried out. Boiling water and SEM qualitative tests are also used. Eventually, the qualitative tests results are digitalized through image processing by MATLAB and compared with the moisture susceptibility results of indirect tensile strength test.For modulus of resilience testing, the results show that this modifier has the maximum impact on Marshall stability, improving it by about 23%. For moisture susceptibility testing, the nanosilica-modified mixture has the maximum effect among anti-stripping additives, with an improvement by about 20%. An investigation into the results of SEM images and boiling water test via MATLAB indicates the high accuracy of SEM images and their results show the most compatibility with the results of quantitative data.
Keywords: Modifier; Moisture susceptibility; Image processing; Scanning electron microscopy (SEM) of bitumen